The impact of weathering operations on archaeological sites in Wasit governorate - والي فريح الركابي ناصر; عباس كريم گهار عبد الكريم (Journal of College of Education, 2020)
Weathering is one of the most important geomorphological processes that exert their influence on archaeological sites in the study area, They are external processes that operate on the surface of the Earth, Thus weathering falls within the classification of morphoclimatic processes because most of them fall under the influence of this climatic conditions with respect to physical and chemical weathering, which depends on the nature of dry and wet climate, While weathering depends on the work of human and the exercise of his activity, An archaeological sites is hardly devoid of the impact of weathering operations either on its surface for archaeological hills or on its walls for historic buildings, This requires archaeological maintenance teams to monitor weathering and impact, and then develop means to limit their activity as much as possible.